Castor oil enhanced effect on fuel ethanol-diesel fuel blend properties. (15th August 2018) - Pinzi, S.; López, I.; Leiva-Candia, D.E.; Redel-Macías, M.D.; Herreros, J.M.; Cubero-Atienza, A.; Dorado, M.P.
Highlights: Castor oil improves stability and solubility of ethanol/diesel fuel blends. Ternary mixture components show antagonistic effects concerning main fuel properties. Models to predict main fuel properties based on mixture composition are provided. A compromise between mixture fuel properties is found using Derringer optimization. A ternary mixture providing optimum main fuel properties has been found. Abstract: Ethanol is a low chain alcohol that could partially substitute diesel fuel to operate compression ignition engines. Its renewable origin and oxygenated structure make ethanol a candidate fuel for internal combustion engines. Main drawbacks of ethanol as a fuel are its low heating value, viscosity, lubricity, cetane number and limited miscibility if mixed with diesel fuel. Additives may enhance its solubility, although with a cost increase. In the present study, castor oil is proposed as an additional component to be added to ethanol-diesel fuel blends. Castor oil and its seeds are not suitable as food neither for humans nor for animals, thus avoiding the possible conflict about the use of land for food or energy, as arises from the use of edible oil/seeds. The presence of a hydroxyl group in the ricinoleic acid increases the polarity of this oil, enhancing ethanol-diesel fuel miscibility. As a result, ternary blends of ethanol, ultra-low sulphur diesel fuel and castor oil have been analyzed considering blend solubility, heating value, kinematic viscosity and cold flow properties, among most critical properties of diesel fuels. Ternary-component mixture prediction models of relevant fuel properties, i.e. kinematic viscosity, cold filter plugging point and high calorific value have been developed. Blend composition that simultaneously optimizes the three fuel properties has been proposed using the desirability function of Derringer. Results from simulation have been experimentally validated, providing a fuel blend composed by diesel fuel, ethanol and castor oil that shows satisfactory values of some of the most significant physical and chemical fuel properties. The presence of a hydroxyl group in the ricinoleic acid provides superior ignitability, lubricant and solubility characteristics with respect to other additives/components, making it a potential suitable candidate as a blend component to enhance ethanol/diesel fuel blends.